1997
DOI: 10.1016/s0304-3959(97)00140-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the blink reflex in burning mouth syndrome

Abstract: To our knowledge, this is the first report on pain-related abnormalities of the eye blink reflex (BR) in a clinical pain patient population. The objective of this study was to evaluate the possible neuropathic mechanisms underlying the burning mouth syndrome (BMS), by means of objective electrophysiological examination of the trigemino-facial system. We studied the BR with stimulation of the supraorbital nerve (SON) with particular emphasis on the occurrence of the pain-related ultralate R3 components, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
2
18

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 14 publications
6
114
2
18
Order By: Relevance
“…The existence of an enhanced blink reflex in some patients with BMS points to a central nervous system alteration correlated to dopaminergic system dysfunction (9). Diminished presynaptic dopaminergic inhibition would increase dopamine release into the interneuronal space, with enhanced neuron excitability manifesting as an increased blink reflex (9,12). Posteriorly, dopaminergic system dysfunction was confirmed in patients with BMS on evaluating dopaminergic function in the brainstem of such patients (13), and on observing a decrease in endogenous dopamine levels in the putamen of individuals with BMS (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of an enhanced blink reflex in some patients with BMS points to a central nervous system alteration correlated to dopaminergic system dysfunction (9). Diminished presynaptic dopaminergic inhibition would increase dopamine release into the interneuronal space, with enhanced neuron excitability manifesting as an increased blink reflex (9,12). Posteriorly, dopaminergic system dysfunction was confirmed in patients with BMS on evaluating dopaminergic function in the brainstem of such patients (13), and on observing a decrease in endogenous dopamine levels in the putamen of individuals with BMS (14).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the existing evidence, menopause can be associated to an increased risk of developing BMS (7). This hypothesis in turn is supported by the good results obtained with oral hormone (estrogen) replacement therapy in application to the symptoms of xerostomia (8). 3.-Lastly, the presence of sensory alterations such as changes in heat tolerance, reduced and altered taste sensation, and increased excitability of the blink reflex in patients with BMS points to the existence of a biological basis related to alterations of both the central and peripheral nervous system (9,10). At present, BMS is regarded as a painful condition involving neuropathic mechanisms, as evidenced by the burning nature of the pain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, reduced levels of NKA in the serum of patients with BMS may reflect a deficiency in the dopaminergic system and some commentators have suggested that such a deficient dopaminergic influence might actually be causative in BMS (11). Electrophysiological examinations in BMS patients indicate an abnormal blink reflex which is under control of dopaminergic inhibitory control through the basal ganglia connection with the facial motor nuclei (12). An abnormal blink reflex is also a common finding in extra-pyramidal disorders such as Parkinson's disease and facial dyskinesias (13,14) where it may be caused by a deficient dopaminergic influence on the brainstem nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies used quantitative sensory testing, electrophysiological methods and functional neuroimaging to assess trigeminal sensory function in patients with BMS: some investigators demonstrated abnormalities of trigeminal pathway function, thus indicating a possible neuropathic aetiology of BMS [48,49]. In a recent study, Lauria and coworkers [50] investigated innervation of the epithelium of the tongue in superficial biopsies from 12 patients who had a 6-month history of clinically definite BMS and healthy persons.…”
Section: Burning Mouthmentioning
confidence: 99%